A Nutraceutical Formula Is Effective in Raising the Circulating Vitamin and Mineral Levels in Healthy Subjects: A Randomized Trial - Nenseth, Hatice Zeynep; Sahu, Aparna; Saatcioglu, Fahri; Osguthorpe, Steven (Frontiers in Nutrition, 2021)
Low levels of nutrient intake are common in industrialized countries. This has negative implications on health and is associated with chronic diseases. Supplementation of vitamins, minerals, and key nutrients to optimal levels may, therefore, be beneficial for individual health and for the health economy. Although the use of supplements has become very common, due to a lack of monitoring, there is very limited data on the efficacy of supplementation with different formulas. In this study, we present the results of a randomized controlled study on the efficacy of a novel formulated nutraceutical, N247, in 250 healthy volunteers aged 26–75 years and a placebo control group (n = 35). The broad-spectrum formulation of N247 includes essential vitamins, minerals, and trace elements that are adequately balanced in regard to synergies and related metabolic functions. Moreover, tolerance, safety, and nutrient availability is an important aspect of daily, long-term use of N247. After 3 months of regular N247 use, levels of vitamins and minerals in serum were significantly increased in the N247 group compared with the control group and a placebo group, with excellent compliance rates. Coupled with additional natural ingredients that aim to increase the potency of the nutrients, N247 may represent a novel and beneficial supplement for individuals with nutritional deficiencies. Clinical Trial Registration:https://clinicaltrials.gov/, identifier: NCT04054505.